Pioglitazone Ameliorates Renal Ischemia-Reperfusion Injury via Inhibition of NF-κB Activation and Inflammation in Rats - Zou, Gaode; Zhou, Zhiyu; Xi, Xiaoqing; Huang, Ruizhen; Hu, Honglin (Frontiers in Physiology, 2021)
Renal ischemia-reperfusion injury (IRI) is considered as a major cause of acute kidney injury. In this study, we investigated the role of the NF-κB signaling pathway and inflammation in the amelioration of renal IRI using pioglitazone. Sprague–Dawley (SD) rats were subjected to bilateral renal artery clamping for 45 min followed by perfusion restoration for establishing a simulated renal IRI model. At 24 h post-operatively, we assessed the serum levels of creatinine and urea nitrogen, expression levels of peroxisome proliferator-activated receptor gamma (PPAR-γ) and NF-κB-related (p-IKK-β and IκB-α) proteins, and mRNA expression levels of the inflammatory cytokines, including TNF-α and MCP-1, in the renal tissue of various study groups. The histopathological evaluation of renal tissue was also conducted. In rat renal tissue, pioglitazone treatment decreased the serum levels of post-renal IRI creatinine and urea nitrogen, as well as necrosis. Furthermore, it elevated the expression of PPAR-γ protein and decreased the expression of NF-κB-related proteins. Pioglitazone also decreased the mRNA expression of TNF-α and MCP-1 in the renal tissue. Thus, pioglitazone ameliorates renal IRI by inhibiting the NF-κB signaling pathway and inflammatory response in rats.